sprayed concrete

JP2026165733APending Publication Date: 2026-10-14TAIHEIYO MATERIALS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025058277
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、良好な材料の混合性を確保し、且つ、低温環境下であっても初期において急結性及び強度発現性にも優れる吹付コンクリートを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165733000001
    Figure 2026165733000001
  • Figure 2026165733000002
    Figure 2026165733000002
  • Figure 2026165733000003
    Figure 2026165733000003
Patent Text Reader

Abstract

To provide sprayed concrete that ensures good material mixing properties and exhibits excellent rapid setting and strength development in the initial stages, even in low-temperature environments. [Solution] A sprayed concrete comprising a concrete composition containing cement, aggregate and gypsum, a rapid-setting admixture and water, wherein the rapid-setting admixture contains calcium aluminate and at least one metal sulfate, and the calcium aluminate has a molar ratio of CaO to Al2O3 as chemical components (CaO / Al2O3) of 1.6 to 2.7 and a molar ratio of SiO2 to MgO (SiO2 / MgO) of 1.1 to 6, and the calcium aluminate content is 55 to 86% by mass based on the total mass of the rapid-setting admixture.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to sprayed concrete. [Background technology]

[0002] In tunnels, mining shafts, and underground spaces, shotcrete is applied to prevent collapse of the excavation surface and to reinforce the ground during or after excavation. Shotcrete ensures adhesion to the target object through its rapid setting properties. To impart rapid setting properties, rapid setting components are mixed into the concrete. For example, powdered rapid setting agents containing calcium aluminate or sodium aluminate as active ingredients can impart strong rapid setting properties, and concrete with higher strength is more likely to be obtained compared to liquid rapid setting agents. In the wet shotcrete method, which is a common method of applying shotcrete, for example, base concrete is prepared by weighing and mixing at least cement, water, and aggregate, and this base concrete is pumped to the shotcrete device via an agitator truck or the like during construction. Inside the shotcrete device, a separately delivered powdered or liquid rapid setting agent is added to the base concrete being pumped, and mixing proceeds in the spray nozzle of the shotcrete device to form shotcrete, which is then sprayed from the nozzle end hole. Another construction method, the dry spraying method, involves weighing and mixing water and at least cement, aggregate, and powdered rapid-setting agent to create dry-mix concrete, which is then air-pressurized from a storage tank or similar container to the spraying device during construction. Inside the spraying device, water is added to the dry-mix concrete as it is being pumped, and mixing continues until it reaches the spraying nozzle to form sprayed concrete, which is then sprayed in the same manner. In both methods, mixing occurs as the rapid-setting components in the spraying device travel from the point where they come into contact with water (water contact point) to the discharge hole at the end of the spraying nozzle, forming the sprayed concrete. The distance used for mixing is usually several tens of centimeters to several meters, and the travel time constitutes the mixing time. Generally, the longer this distance, the more the mixing progresses, the higher the mixability, and the easier it is to obtain sprayed concrete that is more uniform in terms of structure and properties.

[0003] To obtain such sprayed concrete, the powdered rapid-setting agent mixed in is generally a mixture of the aforementioned rapid-setting components with auxiliary agents to adjust various properties. For example, a typical conventional powdered rapid-setting agent (see, for example, Patent Documents 1 and 2) that is highly alkalinized, is made by combining calcium aluminate with a high CaO content as a chemical component, gypsum to accelerate hardening, and sodium aluminate to enhance initial strength development, and sodium carbonate to accelerate setting, etc. The primary objective is to provide high rapid-setting properties and early strength development. As a result, setting occurs in a very short time after the rapid-setting agent comes into contact with water. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2012-121763 [Patent Document 2] Patent No. 5129955 [Overview of the project] [Problems that the invention aims to solve]

[0005] While sprayed concrete mixed with powdered rapid-setting agents is used at construction sites throughout the year, its adhesion and rapid-setting properties generally decrease in low-temperature environments such as winter. A decrease in the adhesion and rapid-setting properties of sprayed concrete can lead to spalling, causing accidents and reducing construction efficiency. Furthermore, with conventional high-strength sprayed concrete, attempting to enhance initial strength development made long-term strength maintenance difficult, or excessive reactivity led to premature hardening during the construction process, worsening workability. Controlling various performance characteristics was also challenging. Moreover, because sprayed concrete hardens very quickly, increasing the mixing distance could easily cause the concrete to solidify during that time, leading to significant spraying problems such as clogging or blockage of spray nozzles. Therefore, sprayed concrete needs to exhibit excellent initial strength development, high mixability to suppress nozzle clogging, and long-term strength maintenance.

[0006] Therefore, the present invention aims to provide sprayed concrete that ensures good material mixing properties and exhibits excellent rapid setting and strength development in the initial stages, even in low-temperature environments. [Means for solving the problem]

[0007] As a result of diligent research into the above-mentioned problems, the inventors of this invention have found that by using a rapid-setting admixture containing calcium aluminate with specific chemical components, sprayed concrete that exhibits high rapid-setting properties even in low-temperature environments can be obtained.

[0008] In other words, the present invention is as follows. [1] A sprayed concrete comprising a concrete composition containing cement, aggregates and gypsum, a rapid-setting admixture and water, wherein the rapid-setting admixture contains calcium aluminate and at least one metal sulfate, and the calcium aluminate has a molar ratio of CaO to Al2O3 as chemical components (CaO / Al2O3) of 1.6 to 2.7 and a molar ratio of SiO2 to MgO (SiO2 / MgO) of 1.1 to 6, and the calcium aluminate content is 55 to 86% by mass based on the total mass of the rapid-setting admixture. [2] The spray concrete described in [1], which is for wet spraying. [3] The sprayed concrete according to [1] or [2], wherein the rapid-setting admixture further comprises an alkali metal carbonate. [4] The sprayed concrete according to [1] or [2], wherein the ratio of fine aggregate to the total volume of aggregate is 45 to 70% by volume. [Effects of the Invention]

[0009] According to the present invention, it is possible to provide sprayed concrete that ensures good material mixing properties and exhibits excellent rapid setting and strength development in the initial stages, even in low-temperature environments. [Modes for carrying out the invention]

[0010] Hereinafter, a preferred embodiment of the present invention will be described in detail. In the present specification, all contents and the like are expressed in terms of solid content and in terms of anhydride.

[0011] The shotcrete of the present embodiment includes a concrete composition containing cement, aggregate and gypsums, a quick-setting admixture, and water.

[0012] [Concrete Composition] The concrete composition includes cement, aggregate, and gypsums. Various types of cement can be used, and examples thereof include various Portland cements such as ordinary, high-early-strength, ultra-high-early-strength, low-heat and moderate-heat Portland cements, eco-cement, ultra-rapid hardening cement, and fly ash cement. One type of cement may be used alone, or two or more types may be used in combination. Portland cement is preferred as the cement. The particle size when using Portland cement is not particularly limited, and examples thereof include those conforming to JIS standard (JIS R 5210:2019) with 2500 cm 2 / g or more.

[0013] Examples of the aggregate include fine aggregate and coarse aggregate. The fine aggregate is not particularly limited as long as it is a fine aggregate that can be used for mortar and concrete. The coarse aggregate is not particularly limited as long as it is a coarse aggregate that can be used for concrete. For both fine aggregate and coarse aggregate, it is easy to ensure a predetermined aggregate strength, and the specific gravity difference with other contained components is small, so that material separation hardly occurs, and thus it is preferable to use an aggregate with a surface-dry density of 2.3 to 2.9 g / cm 3 . Specific examples of such aggregates include, for fine aggregates, natural aggregates such as silica sand and limestone sand, and crushed sand of andesite, sandstone, basalt and the like, and for coarse aggregates, crushed stone and gravel of silica stone, limestone, andesite, sandstone, basalt and the like. One type of aggregate may be used alone, or two or more types may be used in combination.

[0014] The content of aggregate in the shotcrete is not particularly limited, but from the perspective of easily achieving excellent pumpability of concrete during construction, the total amount of fine aggregate and coarse aggregate is preferably 300 to 570 parts by mass, more preferably 380 to 550 parts by mass, and even more preferably 420 to 520 parts by mass, relative to 100 parts by mass of cement content. When fine aggregate and coarse aggregate are used in combination, the fine aggregate ratio ([volume of fine aggregate / volume of total aggregate] × 100) relative to the volume of total aggregate is preferably 45 to 70% by volume, more preferably 50 to 68% by volume, and even more preferably 55 to 65% by volume. If the fine aggregate ratio of the aggregate is within the above range, the pumpability during construction is further excellent, and the initial and long-term strength development properties are further improved.

[0015] Examples of gypsums include anhydrous gypsum, hemihydrate gypsum, and dihydrate gypsum. As the gypsums, anhydrous gypsum is preferred from the viewpoint of further improving the strength development property. The gypsums may be used singly or in combination of two or more kinds. From the viewpoint of further improving the initial strength development, the fineness of the gypsums is 3200 to 18000 cm in terms of Blaine specific surface area 2 / g is preferred, 5000 to 15000 cm 2 / g is more preferred, 5500 to 14000 cm 2 / g is even more preferred, 7000 to 12000 cm 2 / g is particularly preferred

[0016] Various admixtures (materials) may be incorporated into the concrete composition within a range that does not impair the effects of the present invention. Examples of the admixtures (materials) include water reducing agents, expansive materials, defoaming agents, waterproofing agents, rust inhibitors, shrinkage reducing agents, thickeners, water retention agents, pigments, water repellent agents, efflorescence preventing agents, fibers, and pozzolanic substances.

[0017] The concrete composition can be prepared by mixing the above-described respective components with a commonly used kneading apparatus, and the apparatus is not particularly limited. Examples of the kneading apparatus include concrete mixers and the like.

[0018] [Quick setting admixture] The rapid-setting admixture contains calcium aluminate and at least one type of metal sulfate.

[0019] Calcium aluminate is an inorganic hydrated active substance whose main chemical components are CaO and Al2O3. In this embodiment, the calcium aluminate has a molar ratio of CaO to Al2O3 (CaO / Al2O3) of 1.6 to 2.7 and a molar ratio of SiO2 to MgO (SiO2 / MgO) of 1.1 to 6. If the molar ratios of CaO to Al2O3 and SiO2 to MgO are outside the above ranges, the rapid setting and adhesion properties in low-temperature environments will decrease. From the viewpoint of obtaining better rapid setting properties, the molar ratio of CaO to Al2O3 is preferably 1.7 to 2.6, more preferably 1.8 to 2.5, and even more preferably 1.9 to 2.3. The molar ratio of SiO2 to MgO is preferably 1.3 to 5, more preferably 1.5 to 4, and even more preferably 1.7 to 3, from the viewpoint of providing superior rapid setting and adhesion in low-temperature environments, as well as improved strength development. Calcium aluminate may contain impurities and other foreign components other than CaO, Al2O3, SiO2, and MgO derived from the raw materials, regardless of their form, as long as they do not hinder the effects of the present invention.

[0020] Calcium aluminate can be crystalline, amorphous, or a mixture thereof. From the viewpoint of obtaining better rapid setting properties, the vitrification rate, which is the degree of amorphousness, is preferably 60% by mass or more, more preferably 80% by mass or more, and even more preferably 95% by mass or more. The fineness of the calcium aluminate is not particularly limited, but in order to obtain appropriate reaction activity when used as a rapid setting admixture in concrete, it is preferably fineness that is similar to or greater than that of the cement in the hydraulic composition to be admixed, for example, a Blaine specific surface area of ​​3000 to 6500 cm². 2 One example of a powderiness level is / g.

[0021] The calcium aluminate content is 55 to 86% by mass, based on the total mass of the rapid-setting admixture. If the calcium aluminate content is outside this range, it becomes difficult to achieve both rapid setting and mixability in low-temperature environments, and the initial strength development is also poor. From the viewpoint of having excellent rapid setting and strength development, and being less likely to cause clogging during spraying, the calcium aluminate content is preferably 60 to 84% by mass, more preferably 65 to 83% by mass, even more preferably 70 to 82% by mass, and particularly preferably 75 to 80% by mass, based on the total mass of the rapid-setting admixture.

[0022] Calcium aluminate can be obtained, for example, by heating a mixture of raw materials—a CaO source, an Al2O3 source, an SiO2 source, and an MgO source—that are blended to obtain the desired molar ratios of CaO and Al2O3, and SiO2 and MgO, until it melts. Furthermore, because differences in the cooling process after heating during manufacturing result in various differences in the structural state of the calcium aluminate after cooling, the degree of amorphization, or vitrification rate, can be adjusted according to cooling conditions such as the cooling rate. The chemical composition and vitrification rate of calcium aluminate can be measured using an X-ray diffractometer by methods such as the calibration curve method and the Rietveld method.

[0023] The rapid-setting admixture of this embodiment contains at least one metal sulfate. Examples of metals include alkali metals, alkaline earth metals, transition metals, and post-transition metals. Preferred metal sulfates include alkali metal sulfates, alkaline earth metal sulfates, and aluminum sulfate. Preferably, the rapid-setting admixture contains at least two types of metal sulfates.

[0024] The alkali metal sulfate is not particularly limited and any type can be used, but it is preferable that it be anhydrous due to its excellent reactivity. Examples of alkali metals include lithium, sodium, and potassium, with sodium being the most preferred. The alkali metal sulfate may be used alone or in combination of two or more types.

[0025] The alkali metal sulfate content is preferably 1 to 20 parts by mass, more preferably 4 to 15 parts by mass, and even more preferably 5 to 10 parts by mass, on an anhydrous basis, per 100 parts by mass of calcium aluminate. When the alkali metal sulfate content is within the above range, the material tends to exhibit excellent rapid setting properties in low-temperature environments and good initial and long-term strength development.

[0026] The type of alkaline earth metal sulfate is not particularly limited and any can be used, but anhydrous sulfates are preferred due to their excellent reactivity. Examples of alkaline earth metals include magnesium and calcium, with calcium being the most preferred. Alkaline earth metal sulfates may be used individually or in combination of two or more types.

[0027] The content of alkaline earth metal sulfates is preferably 12 to 50 parts by mass, more preferably 13 to 40 parts by mass, even more preferably 13.5 to 30 parts by mass, and particularly preferably 14 to 25 parts by mass, on an anhydrous basis, per 100 parts by mass of calcium aluminate. When the content of alkaline earth metal sulfates is within the above range, excellent strength development from the initial stage to the long term is likely to occur.

[0028] Aluminum sulfate may be in any form, including 16-hydrate and anhydrous forms, with 16-hydrate being preferred. The aluminum sulfate content is preferably 10 parts by mass or less on an anhydrous basis per 100 parts by mass of calcium aluminate, more preferably 8 parts by mass or less, and even more preferably 5 parts by mass or less. If aluminum sulfate is included, its content may be 0.5 parts by mass or more per 100 parts by mass of calcium aluminate. If the aluminum sulfate content is within the above range, it is easier to ensure strength development even when rapid setting is enhanced in a low-temperature environment. Aluminum sulfate may not be substantially included, meaning that the aluminum sulfate content is 0.5 parts by mass or less on an anhydrous basis per 100 parts by mass of calcium aluminate, and preferably 0.1 parts by mass or less.

[0029] Alkali metal carbonates may be used individually or in combination of two or more. The particle size of the alkali metal carbonates is not particularly limited; for example, a Blaine specific surface area of ​​approximately 3000 to 6500 cm² is acceptable. 2 Powders of / g can be used. The alkali metal carbonate content is preferably 10 parts by mass or less on an anhydrous basis, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, per 100 parts by mass of calcium aluminate. If alkali metal carbonate is included, its content may be 0.5 parts by mass or more per 100 parts by mass of calcium aluminate. If the alkali metal carbonate content is within the above range, the initial strength development will be further improved. Alkali metal carbonate may not be substantially included, and substantially not included means that the alkali metal carbonate content is 0.5 parts by mass or less on an anhydrous basis per 100 parts by mass of calcium aluminate, and preferably 0.1 parts by mass or less.

[0030] The rapid-setting admixture of this embodiment may contain various admixtures (materials) to the extent that the effects of the present invention are not impaired. Examples of admixtures (materials) include various pozzolanic powders such as fly ash, silica fume, and slag powder, as well as thickeners and surfactants.

[0031] The rapid-setting admixture according to this embodiment is manufactured by mixing the above-mentioned components. The mixing method is not particularly limited, and a general-purpose mixer such as a tilt mixer, pan mixer, twin-screw mixer, grout mixer, Hobart mixer, or omni mixer can be used.

[0032] The amount of rapid-setting admixture is preferably 3 to 25 parts by mass, more preferably 5 to 23 parts by mass, and even more preferably 7 to 20 parts by mass, per 100 parts by mass of cement. If the amount of rapid-setting admixture added is within the above range, good rapid-setting properties can be easily obtained even in low-temperature environments, initial strength development is even better, and blockage during spraying work is less likely to occur.

[0033] [Sprayed concrete] Shotcrete may be manufactured by a wet spraying method, for example, in which each material except for the rapid-setting admixture is mixed with water in a concrete mixer to form a base concrete, and the base concrete and rapid-setting admixture are mixed at the tip of a spraying nozzle and sprayed. Alternatively, it may be manufactured by a dry spraying method, in which each material including the rapid-setting admixture is mixed to form a base composition, and the base composition and water are mixed at the tip of a spraying nozzle and sprayed. Shotcrete is preferably manufactured by a wet spraying method from the viewpoint that dust and rebound are more easily reduced and each material can be mixed more uniformly.

[0034] The amount of water in the sprayed concrete of this embodiment can be appropriately adjusted depending on factors such as the purpose and location of use. The water content is preferably 35 to 55 parts by mass, more preferably 40 to 52 parts by mass, and even more preferably 42 to 50 parts by mass, per 100 parts by mass of cement. When the water content is within the above range, the initial and long-term strength development and adhesion are further improved.

[0035] The shotcrete of the present embodiment complies with the "Standard Specifications for Concrete Structures" of the Japan Society of Civil Engineers, "Quality Standards for Accelerators for Shotcrete", Annex "Test Method for Flash Setting Time by Penetration Resistance of Mortar Containing Accelerator", under an environment of 10°C, with a cross-sectional area of 0.125cm 2 The penetration resistance value measured using a Proctor needle is 1N / mm at 25 seconds after the addition of the quick-setting admixture 2 or more, more preferably 2N / mm 2 or more, and even more preferably 2.5N / mm 2 or more. When the penetration resistance value is within the above range, the initial quick-setting property is favorable, which facilitates early work after adhesion. In the penetration resistance test, for shotcrete containing coarse aggregate, the total content corresponding to the sum of coarse aggregate and fine aggregate is all converted to the content of fine aggregate, without including coarse aggregate, and the measurement is performed using a base mortar adjusted to a mortar mix without changing other components and their contents.

[0036] The shotcrete of the present embodiment, when hardened, has a compressive strength at an age of 4 hours measured under an environment of 10°C in accordance with JSCE Standard JSCE-G561:2010 "Test Method for Early Strength of Shotcrete by Pullout Method" of 1.5N / mm 2 or more, more preferably 2N / mm 2 or more, and even more preferably 2.5N / mm 2 or more. If the compressive strength at the age of 4 hours measured under a 10°C environment is within the above range, sufficient strength can be obtained at an early stage, so that the construction site is further reinforced.

[0037] The shotcrete of the present embodiment ensures good quick-setting performance and material miscibility, and is also excellent in early strength development. Therefore, the shotcrete of the present embodiment can be suitably used for spraying on tunnel wall surfaces, slopes, environments with spring water, environments with soft ground, and the like. [Examples]

[0038] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. Unless otherwise specified, the examples were conducted under conditions of 10±1℃. In the examples, all content and other figures are based on solid content and anhydrous weight.

[0039] [Preparation of calcium aluminate] Using commercially available industrial chemicals CaCO3, Al2O3, SiO2, and MgO, the materials were weighed and blended to obtain the calcium aluminate with the following molar ratios of CaO and Al2O3 (CaO / Al2O3, C / A ratio) and SiO2 and MgO (SiO2 / MgO). A Henschel mixer was used to prepare the raw material mixture. This raw material mixture was heated in an electric furnace at approximately 1600°C ± 50°C for 60 minutes. Except for some samples, the heated samples were immediately removed from the furnace after the heating time. The surface of the removed heated samples was rapidly cooled by blowing nitrogen gas at a maximum flow rate of approximately 30 mL / second to obtain cooled samples. The vitrification rate of the cooled samples was adjusted by blowing nitrogen gas at a flow rate lower than the maximum value. Each cooled sample was crushed in an all-steel ball mill and subjected to a classifier to obtain a Blaine specific surface area of ​​approximately 5400 cm². 2 The grains were sized to / g. The vitrification rate of calcium aluminate was determined by using a powder X-ray diffractometer to quantify the mass of each mineral contained in calcium aluminate clinker with mass M1 using the internal standard method, etc., and calculating the total mass of the quantified mineral phases; M2. The remainder was considered to be the pure glass phase, and the vitrification rate was calculated using the following formula. Vitrification rate (mass%)={1-(M2 / M1)}×100

[0040] [material] Calcium aluminate (abbreviations CA1-6): Chemical composition is shown in Table 1, Blaine specific surface area 5400 cm². 2 / g, vitrification rate of 99% or more Calcium sulfate reagent (abbreviation CS): Anhydrous gypsum Aluminum sulfate reagent (abbreviation AS): Aluminum sulfate hecahydrate Sodium sulfate reagent (abbreviation NS): Anhydrous Glauber's salt Sodium carbonate reagent (abbreviation NC) Cement: Ordinary Portland cement, Blaine specific surface area 3200 cm² 2 / g, density 3.15g / cm 3 Fine aggregate: Limestone fine aggregate (surface dry density: 2.65g / cm 3 , center grain size; 0.6mm) Coarse aggregate: Crushed stone (surface dry density: 2.74 g / cm³) 3 , center particle size 5~15mm) Gypsum: Anhydrous gypsum, Brain specific surface area 11000cm 2 / g

[0041] [Table 1]

[0042] [Preparation of rapid-setting admixture] The rapid-setting admixture was prepared by mixing each material in the proportions shown in Table 2 and mixing them in a Henschel mixer for 1 minute.

[0043] [Table 2]

[0044] [Preparation of base concrete] A base concrete was prepared by mixing 12 parts by mass of gypsum, 265 parts by mass of fine aggregate, and 182 parts by mass of coarse aggregate with 100 parts by mass of cement, then adding 45 parts by mass of water and mixing in a concrete mixer for 2 minutes.

[0045] [Preparation of sprayed concrete] Immediately after mixing the base concrete, it was placed in a supply tank and pumped from there to the spraying device via a resin hose approximately 10m long and 6cm in inner diameter. The spraying device is a commercially available product with a basic configuration consisting of a 2-inch inner diameter supply pipe through which the base concrete is pumped, a cylindrical side pipe connected to the side of the supply pipe at an angle of approximately 30 degrees for supplying additives (rapid-setting admixtures) to the base concrete, and a 2-inch inner diameter (tip hole diameter) spray nozzle for spraying the concrete. The side pipe for supplying additives was formed by connecting a steel T-shaped pipe (three-way pipe) between the main supply pipe and the spray nozzle. The main supply pipe and the spray nozzle were connected to two pipe openings located on a straight line of the T-shaped pipe, and the supply pipe for the separately delivered rapid-setting admixture was connected to the remaining pipe opening. Mixing of the base concrete and the rapid-setting admixture occurred between the point where the rapid-setting admixture was added to the base concrete in the T-shaped pipe (the point where the base concrete and rapid-setting admixture meet) and the end of the spray nozzle hole, with this distance (hereinafter referred to as the mixing distance) being 2m. A predetermined amount of the rapid-setting admixture was air-pressurized by compressed air and added to the base concrete being pumped in the spraying device. The added concrete was mixed as it traveled the predetermined mixing distance, producing sprayed concrete. The amount of rapid-setting admixture added is shown in Table 2.

[0046] Each test evaluation was conducted according to the following method. The test results are shown in Table 3. [Assessment of rapid onset] In the base concrete mix design, the amount equivalent to the total content of coarse and fine aggregates in each mix was entirely replaced with fine aggregate, eliminating the coarse aggregate. A base mortar was then prepared using the same procedure as for the base concrete, without changing the other components or their contents. The resulting base mortar was then mixed with rapid-setting admixtures in the proportions shown in Table 1 and mixed in a high-speed mixer for 5 seconds to produce a mortar mixture. The rapid setting properties of the mortar mixture were evaluated by measuring the Proctor penetration resistance values ​​25 seconds, 45 seconds, 60 seconds, and 180 seconds after the addition of the rapid setting admixture. The method for measuring the Proctor penetration resistance was in accordance with the Japan Society of Civil Engineers' Standard Specifications for Concrete, "Quality Standards for Rapid Setting Agents for Sprayed Concrete," Appendix "Method for Measuring Instant Setting Time by Penetration Resistance of Mortar with Rapid Setting Agent Added," using a cross-sectional area of ​​0.125 cm². 2 A Proctor needle was used. The measurement results of the penetration resistance are shown in Table 3. Also, in the table, ">16 (N / mm 2 The description states that the Proctor needle could be driven in, but the measurement limit of the equipment used this time was (maximum 16 N / mm²). 2 This exceeds the specified limit. If the measurement limit of the equipment used is exceeded, further measurements are not performed and it is indicated with "-".

[0047] [Evaluation of Strength Development of Sprayed Concrete] The mixing distance was set to 2m, and the prepared sprayed concrete was immediately sprayed into a molding formwork with inner dimensions of 30 × 40 × 20 cm to fill the formwork. This was placed in a constant temperature chamber at 10°C (±1°C) for a predetermined time, and cylindrical specimens with a diameter of 5 cm and a height of 10 cm were taken from the hardened concrete in the formwork using a core drill to obtain specimens that were 28 days old. The uniaxial compressive strength of these 28-day-old specimens was measured using a hydraulic compressive strength tester. In addition, sprayed concrete prepared in the same manner using the formwork and embeddings specified in the Japan Society of Civil Engineers standard JSCE-G561:2013 was subjected to a pull-out test in accordance with JSCE-G561:2013. The compressive strength of the sprayed concrete at 4 hours and 24 hours was measured by this test. The results of the strength measurements for each specimen are shown in Table 3.

[0048] [Evaluation of the adhesion properties of sprayed concrete] Using the spraying apparatus described above, the obtained sprayed concrete was immediately used for spraying work. It was sprayed 10 meters towards a 3-meter square concrete slab surface with a thickness of 9 mm, which was vertically positioned approximately 100 cm away from the nozzle end of the spraying apparatus. 3The sprayed concrete was applied at a flow rate of [number] hours. The adhesion of the sprayed concrete was evaluated by visual observation as follows: Concrete that remained attached to the flat surface without sagging or spalling was judged to have "good" adhesion, while all other conditions, or cases where spraying was practically impossible, were judged to have "poor" adhesion. The results are shown in Table 3.

[0049] [Evaluation of the mixability of sprayed concrete] Under conditions equivalent to those used for the adhesion evaluation, spraying was performed for 5 minutes at a mixing distance of 2m. Afterward, the pumping supply of base concrete was stopped for 30 minutes to interrupt the spraying process. Then, the pumping supply of base concrete was resumed, and spraying was performed again. At this time, depending on the mixing distance, if there were pumping problems such as narrowing or blockage in the T-pipe or the pumping path of the spraying device, or spraying problems such as a decrease in the amount of sprayed concrete discharged, it was judged as "clogging / blockage present." Conversely, if these phenomena were not observed, pumping was smooth, and there was no fluctuation in the amount of sprayed concrete, it was judged as "no clogging / blockage." These results are shown in Table 3. 10m 3 When sprayed at a flow rate of / hour and the mixing distance was 2m, the mixing time was approximately 1.4 seconds.

[0050] [Table 3]

[0051] The sprayed concrete using the rapid-setting admixture in the example could be pumped without clogging, exhibited good adhesion even in low-temperature environments, and showed excellent initial rapid-setting and strength development. On the other hand, the sprayed concrete using the rapid-setting admixture in the comparative example showed clogging and poor adhesion, and did not show excellent initial rapid-setting or strength development.

Claims

1. A concrete composition containing cement, aggregates and gypsum, a rapid-setting admixture, and water, The rapid-setting admixture comprises calcium aluminate and at least one type of metal sulfate. The aforementioned calcium aluminate contains CaO and Al as chemical components. 2 O 3 The molar ratio of the content (CaO / Al 2 O 3 ) is 1.6 to 2.7, SiO 2 and the molar ratio of MgO content (SiO 2 The ratio of MgO is between 1.1 and 6. A sprayed concrete wherein the calcium aluminate content is 55 to 86% by mass based on the total mass of the rapid-setting admixture.

2. The sprayed concrete according to claim 1, which is for wet spraying.

3. The sprayed concrete according to claim 1 or 2, wherein the rapid-setting admixture further comprises an alkali metal carbonate.

4. The sprayed concrete according to claim 1 or 2, wherein the ratio of fine aggregate to the total volume of aggregate is 45 to 70% by volume.

Citation Information

Patent Citations

  • Itonohinshitsuhyokasochi

    JP1976029955A

  • Quick setting agent for spraying and sprayed concrete using the same, and spraying method

    JP2012121763A